Physicochemical Properties, Nutritional Composition, And Sensory Acceptance Of Chicken Meat Sausages With Chia Seed Powder Substitution - Nurhani Fatihah Mohd Hanifah; Hanis Nadia Yahya; Norlelawati Arifin (USIM Press, 2024)
Vol. 7 No. 1 (2021)